PENGENDALIAN RAYAP COPTOTERMES CURVIGNATHUS HOLMGREN DENGAN UMPAN RAYAP HEXAFLUMURON BENTUK BRIQUETTE PADA PERKEBUNAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) - Toni, Iliyin; Diba, Farah; haida, Nur (JURNAL HUTAN LESTARI, 2016)
The highest damage from insect as a pest on oilpalm plantation was found by subterranean termite Coptotermes curvignathus Holmgren. This termite’s attack the oilpalm from the trunk, leaf, crown and can made the oilpalm die within three weeks after attack on the apical growth. Termites control in oil palm is using the spraying chemicals technique. This is a contact poison and kills the termites when they have contact with the chemicals. Termite’s colony in soil still alive and can attack the other oilpalm. The new method for termites control is needed. Termite baiting system is an alternative for the termites control in oilpalm plantation. The advantage of termites baiting system is this bait work for termite’s colony elimination, more environmentally friendly, less use of chemicals, and packaged in an effective form. The research purposes to evaluate the termites bait with active ingredients Hexaflumuron to control termites in oilpalm plantation. The research was conducted in the area of oilpalm plantations in Purun district belong to PT. Peniti Sungai Purun, Mempawah Regency, West Kalimantan Province. One termites bait with briquettes formulation was put in one oilpalm which heavily attack by termites. The bait weight was 30 gram. Sample of oilpalm was three oilpalm from three blocks. Monitoring the bait was conducted every 7 days. The results showed all the bait was consumed by termites. Average value of termites bait consumption was 98.3% and all the termites was totally eliminated after 28 days. Monitoring the presence of termites attack after treatment was conducted for two month. The results showed no termites come to attack the oilpalm again. Hexaflumuron is able to eliminate the termites in oilpalm plantations. Key words :Coptotermes curvignathus, hexaflumuron, oilpalm plantations, termites bait